Application of accelerated heteronuclear single quantum coherence experiments to the rapid quantification of monosaccharides and disaccharides in dairy products - Fels, Lea (Magnetic resonance in chemistry : MRC, 2022)
© 2022 The Authors. Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd.